Evaluation of physiological quality of seed on yield of yellow and black soybean treated with biological seed coating - Kadapi, Muhamad; Salim, Priscilla Olga; Sumadi, Sumadi (Kultivasi, 2023)
The demand for soybeans as one of cereal commodities increases every year, however, to meet the production and demand level is still challenging in Indonesia. One of the causes of low soybean production is stress during cultivation, lack of nutrients, or poor quality of soybean seeds. One solution is to increase seed protection by coating the seeds with an environmentally friendly biological seed coating. This study aims to obtain the best biological seed coating for increasing soybean seed viability, vigor, and yield. The research was conducted at the Faculty of Agriculture Experimental Station of Universitas Padjadjaran, Jatinangor from August to November 2021. Two sets of experimental design were employed in this study, a Completely Randomized Design for the viability and vigor parameters in laboratory, and a Randomized Block Design with four replications for evaluation of the yield components in the field. The experiment was carried out with a combination of soybean cultivar and biological seed coating. The cultivars used in this study were Anjasmoro cv. (yellow) and Detam-4 cv. (black) and the biological seed coatings were B. subtilis, Trichoderma sp., and Rhizobium sp. Post-hoc test after F-test used Least Significance Different (LSD) with a significant level of 5%. The results showed that the application of the three biological seed coatings was not significantly affect seed physiological traits. However, the seed coating treatments increased the number of seeds per plant and seed weight per plant in yellow soybeans. Meanwhile, the application of B. subtilis and Rhizobium sp. in black soybeans increased the number of seeds per plant and the weight of seeds per plant. The best biological seed coating in this experiment was B. subtilis.